ANALISIS PENGARUH VARIASI KATUP TETAP RPM BERUBAH DAN VARIASI RPM TETAP KATUP BERUBAH PADA POMPA SERI, PARAREL, DAN TUNGGAL - Citrakara Upendra Sneha Bhandana Himawan; Johan Wayan Dika; Agus Dwi Putra (Universitas Islam Malang, 2023)
A pump is a tool that functions to drain, circulate and move liquid fluids by applying pressure and speed from one place to another. On internal combustion engines, the purpose of testing is to determine the performance characteristics of internal combustion engines. This research can be used as teaching material and discussion by students in the fields of pumps, gasoline motors, and diesel motors. Each test with a different treatment will give a different outcome value. The result is that in the pump test, the output value is influenced by the treatment of the throttle and engine speed, whereas in the testing of diesel and gasoline engines the output value is affected by the treatment of the visor and throttle.